Determination of Stratiform Cloud Formation and its Effect upon Glacial Ablation at Linnébreen, Svalbard for the Summer of 2005 - Carlos D. Szembek (Arctic Data Center, 2013)
The intent of this study is to investigate the formation and organization of Arctic stratiform clouds due to their critical role as a climate forcing mechanism in a warming Polar Basin as well as their impact upon the glacial mass balance. For four weeks in the summer of 2005, meteorological and insolation data were collected at the high-arctic glacier Linnébreen in Svalbard, Norway as part of an NSF funded Research Experience for Undergraduates program. The first portion of this project involves modeling the atmospheric circulation over several nested domains; these domains are scaled from the western Atlantic Arctic region down to the 1km-scale resolving the glacial melt-water basin using the Polar Fifth Generation Mesoscale Model (Polar MM5). Cases were selected based upon dates preceding significant glacial ablation events. The second component of this research focuses upon correlating glacial ablation data with the meteorological observations. With the assistance of the Polar MM5 it is possible to simulate these occurrences, which reveal the moisture and temperature advection as well as the heat budget for the Svalbard region.